Performance of soybean varieties in hilly areas - Shaheenuzzamn, M; Biswas, A; Karim, MM; Islam, MK (Bangladesh Agronomy Journal, 2015)
Abstract not available Bangladesh Agron. J. 2014, 17(1): 107-108